Pendampingan UMKM Memperoleh Sertifikat Halal di Kecamatan Anggeraja Enrekang - Nacing, Nursyawal; Elihami, Elihami (LP2M Universitas Muhammadiyah Enrekang, 2024)
The Halal Product Assurance Organizing Agency (BPJPH) of the Ministry of Religious Affairs of the Republic of Indonesia issued a regulation that all MSME products must be halal-certified by 2024. Halal certification is essential to ensure consumers feel safe and do not violate Islamic rules. The knowledge and understanding of MSMEs about halal certification and business identification numbers (BIN) is still relatively minimal, indicated by the low number of MSMEs that have halal certification. To increase the number of MSME businesses, This service activity aimed at 20 MSMEs in the Anggeraja sub-district aims to facilitate direct socialization and halal certification of MSMEs. The halal certification authorization process currently uses an online system preceded by halal understanding and NIB socialization to facilitate and assist SMEs in obtaining halal certification. From this activity, it is hoped that MSMEs in Anggeraja Enrekang District can develop better and faster. This service activity is in collaboration with the Office of Cooperatives, SMEs, Manpower and Transmigration of Enrekang Regency, and BPJPH of the Ministry of Religion of Enrekang Regency